A new species of Vernonia (Asteraceae, Vernonieae) from the state of Oaxaca, Mexico - Redonda-Martínez, Rosario; Villaseñor, José Luis; Campos-Villanueva, Alvaro (Phytotaxa, 2016)
A new species of Vernonia (Asteraceae, Vernonieae) is described from mountain cloud forest, Pinus forest and Pinus–Quercus forest in the State of Oaxaca, Mexico. Typical characters of this species are the lax corymbiform inflorescences, formed by 3–10 heads on peduncles > 4.5 cm long, and the lanceolate or elliptic-ovate shape of leaves. A key to the Mexican species of Vernonia is included.